Electrolyte solution and power storage device using same

By using a compound with cyclopropane ring or aziridine ring as an electrolyte, a low viscosity electrolyte solution is formed, which solves the problems of high resistance and safety at low temperatures, and achieves excellent electrical characteristics and safety of the power storage element at low temperatures.

CN119731756APending Publication Date: 2025-03-28PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380059802.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-23
Filing Date
2023-08-04
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The resistance value of the existing electrolyte is high at low temperatures, and acetonitrile has safety problems such as combustion and toxic gas production.

Method used

A compound having 11 or less heavy atoms and having one or more cyclopropane rings or aziridine rings is used as the electrolyte in the non-aqueous solvent to form an electrolyte with a low viscosity, thereby providing low resistance and excellent electrical characteristics at low temperatures.

Benefits of technology

It achieves the low internal resistance and excellent electrical characteristics for the power storage components at low temperatures, while avoiding the generation of toxic gases during combustion and improving safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119731756A_ABST
    Figure CN119731756A_ABST
Patent Text Reader

Abstract

An electricity storage element is configured using an electrolyte solution that is provided with a non-aqueous solvent and an electrolyte dissolved in the non-aqueous solvent, and the non-aqueous solvent contains a first compound having 11 or less heavy atoms and one or more cyclopropane rings or aziridine rings. As a result, it is possible to provide an electricity storage element which has low resistance at low temperatures and can exhibit excellent electrical characteristics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to an electrolyte solution and an electric storage device using the same. Background Art

[0002] Storage elements are used in a variety of applications. For example, electric double layer capacitors and lithium ion capacitors are used as small power sources for backup of semiconductor memories, etc. Since these capacitors are assumed to be used under severe conditions, it is important for the electrolyte used to have the characteristics of being able to operate the capacitor stably for a long time in a wide temperature range from low to high temperatures.

[0003] Patent Document 1 discloses an electrolytic solution for an electric double layer capacitor, in which tetraethylammonium tetrafluoroborate, which is an aliphatic quaternary ammonium salt and serves as an electrolyte, is dissolved in propylene carbonate, which serves as an organic solvent.

[0004] Patent document 2 discloses a capacitor electrolyte, wherein a quaternary ammonium salt or a lithium salt is used as an electrolyte, and a mixed solvent containing acetonitrile is used as an organic solvent. The acetonitrile has the following characteristics: the viscosity at room temperature is 0.34 mPa·s, which is very low, and therefore, it has the characteristic of being able to reduce the resistance value of the element at low temperature.

[0005] The above-mentioned propylene carbonate and acetonitrile are also used as electrolytes for non-aqueous electrolyte secondary batteries.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2000-114105

[0009] Patent Document 2: International Publication No. 2013 / 146136 Summary of the invention

[0010] Problem that the invention aims to solve

[0011] However, propylene carbonate has a slightly high viscosity of 2.5 mPa·s at room temperature, and has a problem of high resistance of components at low temperatures. Acetonitrile has a low viscosity of 0.34 mPa·s at room temperature, and has a characteristic of suppressing resistance of components at low temperatures, but has a problem of generating hydrogen cyanide gas due to combustion in accidents, etc., and its use is limited due to safety issues.

[0012] Solutions for solving problems

[0013] One aspect of the present disclosure relates to an electrolyte solution including a nonaqueous solvent and an electrolyte dissolved in the nonaqueous solvent, wherein the nonaqueous solvent contains a first compound having 11 or less heavy atoms and one or more cyclopropane rings or aziridine rings.

[0014] Another aspect of the present disclosure relates to an electric storage element having the above-mentioned electrolytic solution.

[0015] Another embodiment of the present disclosure relates to a compound having the following structure,

[0016]

[0017] Effects of the Invention

[0018] According to the electrolytic solution of the present disclosure, it is possible to provide an electric storage element that has a low resistance particularly at low temperatures and exhibits excellent electric characteristics.

[0019] The novel features of the present invention are described in the appended claims, but the present invention, both in terms of configuration and content, together with other objects and features of the present application, should be further fully understood from the following detailed description with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 A partially cutaway perspective view schematically illustrating an internal structure of a secondary battery according to an embodiment of the present disclosure. DETAILED DESCRIPTION

[0021] Hereinafter, examples are given to illustrate the embodiments of the electrolyte and the storage element of the present disclosure, but the present disclosure is not limited to the examples described below. In the following description, specific numerical values ​​and materials are sometimes exemplified, but other numerical values ​​and materials can also be applied as long as the effects of the present disclosure are obtained. In the following description, when the examples involve the lower limit and upper limit of the numerical values ​​of specific physical properties, conditions, etc., as long as the lower limit does not become above the upper limit, any of the lower limits of the examples and any of the upper limits of the examples can be arbitrarily combined. When multiple materials are exemplified, one can be selected from them and used alone, or two or more can be combined and used.

[0022] The storage element includes a non-aqueous electrolyte capacitor, a non-aqueous electrolyte secondary battery, etc. The storage element can be an element that utilizes both a Faraday reaction and a non-Faraday reaction (i.e., has the properties of both a capacitor and a secondary battery). The non-aqueous electrolyte capacitor includes a double-layer capacitor, a lithium-ion capacitor, etc. The non-aqueous electrolyte secondary battery includes a lithium-ion secondary battery, a lithium metal secondary battery, etc. The capacitor is also called a "condenser".

[0023] The electrolyte of one embodiment of the present disclosure is a non-aqueous electrolyte, which has a non-aqueous solvent and an electrolyte dissolved in the non-aqueous solvent. The non-aqueous solvent can be an organic solvent. The non-aqueous solvent contains a first compound. The first compound is a compound having less than 11 heavy atoms and more than one cyclopropane ring or aziridine ring. The first compound has a low viscosity, and the viscosity at room temperature can be less than 0.6 mPa·s. In addition, the first compound does not contain a cyanide group, so even if it burns, no toxic hydrogen cyanide gas is produced. The non-aqueous solvent contains the first compound, so the storage element exhibits excellent electrical properties even at low temperatures. Specifically, a safe non-aqueous electrolyte capacitor, a non-aqueous electrolyte secondary battery, etc. with low internal resistance and excellent conductivity, which does not produce toxic gases when burned, is provided.

[0024] The heavy atom refers to an atom other than a hydrogen atom and a helium atom, and specific examples thereof include heteroatoms such as a nitrogen atom and an oxygen atom, and a carbon atom.

[0025] The first compound is preferably represented by any of Compounds 1 to 3 having the following structures.

[0026]

[0027] When the first compound is Compound 1, Compound 2, or Compound 3, the viscosity is lowered, and thus the resistance of the electric storage element at low temperature can be further reduced.

[0028] Any of Compounds 1 to 3 may be used alone, or two or more of Compounds 1 to 3 may be mixed and used.

[0029] The content of the first compound in the electrolyte is preferably 5% by mass or more and 80% by mass or less, can be 5% by mass or more and 50% by mass or less, can be 5% by mass or more and 30% by mass or less. When the content of the first compound is 5% by mass or more, the viscosity of the mixed nonaqueous solvent as a whole is fully reduced, and the improvement of the resistance at low temperatures is sufficient. On the contrary, when the content of the first compound is 80% by mass or less, the precipitation of electrolyte (for example, quaternary ammonium salt or lithium salt) is suppressed, and the characteristic of the storage element becomes better. In addition, the content of the first compound in the nonaqueous solvent can be 3% by mass or more and 50% by mass or less, can be 3% by mass or more and 30% by mass or less, can be 3% by mass or more and 20% by mass or less.

[0030] The electrolyte disclosed in the present invention is an electrolyte in which a quaternary ammonium salt or a lithium salt is dissolved in a non-aqueous solvent. By making the non-aqueous solvent contain the first compound, the viscosity is lower than that of the electrolyte using propylene carbonate. Therefore, the resistance of the storage element at low temperature becomes smaller. In addition, since there is no cyanide group in the molecular structure, there is no possibility of generating hydrogen cyanide gas due to combustion during an accident.

[0031] The nonaqueous solvent may contain other compounds in addition to the first compound. As the other compound, a second compound selected from the group consisting of γ-butyrolactone, vinylene carbonate, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate and 3-methylsulfolane may be used.

[0032] The electrolyte in the electrolytic solution may be a quaternary ammonium salt or a lithium salt. As the quaternary ammonium salt, a salt composed of a tetraalkylammonium ion and an anion is desirable.

[0033] As the tetraalkylammonium ion, at least one of tetramethylammonium ion, trimethylethylammonium ion, triethylmethylammonium ion, tetraethylammonium ion, tetrabutylammonium ion, diethyldimethylammonium ion, ethyltrimethylammonium ion and the like can be used.

[0034] Examples of anions constituting the quaternary ammonium salt or lithium salt include Cl - 、BF4 - PF6 - 、ClCO4 - CF3SO3 - 、N(FSO2)2 - 、N(CF3SO2)2 - 、N(C2F5SO2)2 - 、C(CF3SO2)3 - .

[0035] As the quaternary ammonium salt, triethylmethylammonium tetrafluoroborate is preferred, and as the lithium salt, LiPF6 is preferred.

[0036] The preferred lower limit of the concentration of the quaternary ammonium salt or lithium salt in the electrolyte disclosed herein is 0.1 mol / L, and the preferred upper limit is 3.0 mol / L. When the concentration of the quaternary ammonium salt or lithium salt is 0.1 mol / L or more, sufficient conductivity can be ensured. When the concentration of the quaternary ammonium salt or lithium salt is 3.0 mol / L or less, the increase in the viscosity of the obtained electrolyte can be suppressed, and a storage element with excellent electrical properties can be obtained. The more preferred lower limit of the concentration of the quaternary ammonium salt or lithium salt is 0.5 mol / L, and the more preferred upper limit is 2 mol / L.

[0037] The manufacturing method of the electrolyte of the present invention is as follows. First, the non-aqueous solvent and the quaternary ammonium salt or the lithium salt are dehydrated. Then, the electrolyte formed by the quaternary ammonium salt or the lithium salt is added to the non-aqueous solvent under a low humidity environment such as a glove box to dissolve it.

[0038] Furthermore, the storage element using the electrolyte prepared herein is also included in the present invention. For example, the double-layer capacitor comprises: a pair of polarized electrodes, a separator sandwiched between the electrodes, an electrolyte, and a container that seals these. The lithium-ion capacitor comprises: a polarized positive electrode, a negative electrode capable of inserting and removing lithium ions, an electrolyte, a separator sandwiched between the electrodes, and a container for storing these. The lithium-ion secondary battery comprises: a positive electrode capable of inserting and removing lithium ions, a negative electrode capable of inserting and removing lithium ions, an electrolyte, a separator sandwiched between the electrodes, and a container for storing these.

[0039] As an example of a storage element, Figure 1 The structure of the nonaqueous electrolyte secondary battery will be described. Figure 1 This is a schematic perspective view of a partially cut-away rectangular nonaqueous electrolyte secondary battery.

[0040] The secondary battery comprises a battery case 4 having a bottom and a square shape, and an electrode group 1 and a non-aqueous electrolyte (not shown) housed in the battery case 4. The electrode group 1 comprises a long strip-shaped negative electrode, a long strip-shaped positive electrode, and a separator sandwiched therebetween. The electrode group 1 is formed by winding the negative electrode, the positive electrode, and the separator around a flat winding core and pulling out the winding core.

[0041] One end of the negative electrode lead 3 is attached to the negative electrode collector of the negative electrode by welding or the like. One end of the positive electrode lead 2 is attached to the positive electrode collector of the positive electrode by welding or the like. The other end of the negative electrode lead 3 is electrically connected to the negative electrode terminal 6 provided on the sealing plate 5 through the gasket 7. The other end of the positive electrode lead 2 is electrically connected to the battery case 4 which also serves as the positive terminal. A resin frame is arranged on the upper part of the electrode group 1 for isolating the electrode group 1 from the sealing plate 5 and isolating the negative electrode lead 3 from the battery case 4. The opening of the battery case 4 is sealed by the sealing plate 5.

[0042] In the present disclosure, as another embodiment, a compound having any of the structures of the following compounds 1 to 3 is included.

[0043]

[0044] Furthermore, as another embodiment, an electrolyte solution additive having any of the structures of the following compounds 1 to 3 is included.

[0045]

[0046] [Example]

[0047] Hereinafter, the present disclosure will be specifically described based on Examples and Comparative Examples, but the present disclosure is not limited to the following Examples.

[0048] [Method for producing compound 1]

[0049] Compound 1 is synthesized by generating intermediate 1 from one of two bromocyclopropane compounds using a Grignard reagent, and then reacting the intermediate 1 with the other bromocyclopropane compound through a Grignard reaction.

[0050] In an inert gas atmosphere, 1-bromo-2-ethylcyclopropane (150 g, 1.01 mol) dissolved in THF (500 mL) was added dropwise to a mixture of magnesium metal (26.9 g, 1.11 mol) and THF (500 mL) for 30 minutes, and stirred at room temperature for 5 hours to prepare a Grignard reagent. It took 30 minutes to drop the Grignard reagent into a mixture of 1-bromo-2,3-dimethylcyclopropane (165 g, 1.11 mol) and THF (500 mL) cooled to -70°C, warmed to room temperature, and stirred for 8 hours. After quenching the reaction solution with water, the organic layer extracted with ethyl acetate was washed with saturated brine, dried with anhydrous sodium sulfate, and the solvent was distilled off under reduced pressure. The obtained liquid was refined by silica gel column chromatography (petroleum ether / ethyl acetate), thereby obtaining compound 1 (97.7 g, 0.707 mol) with a yield of 70%.

[0051] [Method for producing compound 2]

[0052] Compound 2 is synthesized through two-step reactions: formation of a cyclopropane ring by a Simmons-Smith reaction and formation of an aziridine ring by an intramolecular cyclization reaction.

[0053] (Formation of cyclopropane ring based on Simmons-Smith reaction)

[0054] In an inert gas atmosphere, 1M diethylzinc / hexane solution (500mL, 0.500mol) and dichloromethane (1000mL) were mixed, cooled to 0°C, and then 5M trifluoroacetic acid / dichloromethane solution (100mL, 0.500mol) was added dropwise over 30 minutes, followed by stirring for 1 hour. While maintaining the reaction solution at 0°C, 1,1-diiodo-2-methylpropane (155g, 0.500mol) dissolved in dichloromethane (500mL) was added dropwise over 30 minutes, and then 1-(methylamino)-3-butene-2-ol (101g, 1.00mol) dissolved in dichloromethane (1000mL) was added dropwise over 30 minutes, followed by stirring at room temperature for 12 hours. After the reaction solution was quenched with 0.1M aqueous ammonium chloride solution, the organic layer extracted with ethyl acetate was washed with saturated brine, dried over anhydrous sodium sulfate, and the solvent was distilled off under reduced pressure. The obtained mixture was purified by silica gel column chromatography (petroleum ether / ethyl acetate) to give 2-isopropyl-α-[(methylamino)methyl]cyclopropanemethanol (59.0 g, 0.375 mol) in a yield of 75%.

[0055] (Formation of aziridine ring based on intramolecular cyclization reaction)

[0056] To a mixed solution of benzene (300 mL) and 2-isopropyl-α-[(methylamino)methyl]cyclopropanemethanol (80.0 g, 0.509 mol), p-toluenesulfonyl chloride (116 g, 0.610 mol) and tetrabutylammonium hydrogen sulfate (34.6 g, 0.102 mol) dissolved in benzene (200 mL) were added and stirred for 30 minutes. Then, a 50% aqueous sodium hydroxide solution (50 mL) was added and stirred at room temperature for 2 hours. After the reaction, the organic layer was separated and the aqueous layer was extracted 3 times with ethyl acetate. The organic layers were combined, washed twice with water and saturated brine, respectively, dried over anhydrous sodium sulfate, and then the solvent was distilled off under reduced pressure. Using silica gel inactivated with triethylamine, the obtained mixture was refined by column chromatography (pentane / ethanol) to obtain compound 2 (49.6 g, 0.356 mol) with a yield of 70%.

[0057] [Method for producing compound 3]

[0058] Compound 3 is synthesized through three-step reactions: formation of aldehyde by Dess-Martin reaction, formation of alkyl adduct by Grignard reaction, and formation of aziridine ring by intramolecular cyclization reaction.

[0059] (Formation of aldehydes based on the Dess-Martin reaction)

[0060] Dess-Martin periodinane (331 g, 0.780 mol) was added to a mixed solution of dichloromethane (2000 mL) and 2-amino-3-methoxybutane-1-ol (71.5 g, 0.600 mol), and stirred at room temperature for 2 days. After the reaction solution was quenched with methanol, it was stirred for 1 hour, and the obtained suspension was filtered, and the filtrate solvent was distilled off under reduced pressure. The obtained mixture was purified by silica gel column chromatography (pentane / ethyl acetate), thereby obtaining 2-amino-3-methoxybutyraldehyde (47.8 g, 0.408 mol) with a yield of 63%.

[0061] (Formation of alkyl adducts based on Grignard reaction)

[0062] After cooling a mixed solution of THF (700 mL) and 2-amino-3-methoxybutyraldehyde (82.0 g, 0.700 mol) to -70 ° C, 2M propylmagnesium bromide / THF solution (700 mL, 1.40 mol) was added dropwise over 30 minutes, warmed to room temperature, and stirred for 8 hours. After quenching the reaction solution with water, the organic layer extracted with ethyl acetate was washed with saturated brine, dried over anhydrous sodium sulfate, and the solvent was distilled off under reduced pressure. The obtained liquid was refined by silica gel column chromatography (petroleum ether / ethyl acetate), thereby obtaining 3-amino-2-methoxyheptane-4-ol (57.6 g, 0.357 mol) with a yield of 51%.

[0063] (Formation of aziridine ring based on intramolecular cyclization reaction)

[0064] In a mixed solution of THF (1500mL) and triphenylphosphine (127g, 0.484mol), diisopropyl azodicarboxylate (93.0mL, 0.484mol) was added dropwise, and stirred at room temperature for 30 minutes. In this mixed solution, a mixed solution of THF (2000mL) and 3-amino-2-methoxyheptane-4-ol (65.0g, 0.403mol) was added dropwise, and after heating and refluxing for 24 hours, the reaction solution was returned to room temperature and the solvent was distilled off under reduced pressure. Diethyl ether was added to the obtained mixture, and after filtering the precipitate, the filtrate solvent was distilled off under reduced pressure. Using silica gel inactivated with triethylamine, the obtained mixture was refined by column chromatography (pentane / ethanol) to obtain compound 3 (41.6g, 0.209mol) with a yield of 72%.

[0065] (Viscosity measurement)

[0066] The viscosity of the compounds 1 to 3 synthesized as described above at room temperature was measured by a viscometer RSM-MV1 manufactured by SMILECo. Compound 1 is 0.46 mPa·s, compound 2 is 0.52 mPa·s, and compound 3 is 0.58 mPa·s, all of which are below 0.6 mPa·s. These values ​​are lower than the viscosity of propylene carbonate commonly used as a solvent for an electrolyte, i.e., 2.5 mPa·s. In addition, diethyl carbonate and dimethyl carbonate are also used as low-viscosity solvents, but their viscosities are 0.8 mPa·s and 0.6 mPa·s, respectively, which are lower viscosities.

[0067] Comparative Example 1

[0068] Triethylmethylammonium tetrafluoroborate was added to propylene carbonate so as to have a concentration of 1.0 mol / L to obtain an electrolyte solution for a capacitor.

[0069] 《Comparative Example 2》

[0070] Triethylmethylammonium tetrafluoroborate was added to a solvent containing 90 parts by weight of propylene carbonate (manufactured by Tokyo Chemical Industry Co., Ltd.) and 10 parts by weight of dibutyl carbonate (manufactured by Tokyo Chemical Industry Co., Ltd.) at a concentration of 1.0 mol / L to obtain an electrolyte solution for a capacitor.

[0071] 《Comparative Example 3》

[0072] Triethylmethylammonium tetrafluoroborate was added to a solvent containing 90 parts by weight of propylene carbonate (manufactured by Tokyo Chemical Industry Co., Ltd.) and 10 parts by weight of pimelic acid (manufactured by Tokyo Chemical Industry Co., Ltd.) at a concentration of 1.0 mol / L to obtain an electrolyte solution for a capacitor.

[0073] 《Example 1》

[0074] Triethylmethylammonium tetrafluoroborate was added to a solvent containing 90 parts by weight of propylene carbonate (manufactured by Tokyo Chemical Industry Co., Ltd.) and 10 parts by weight of Compound 1 so as to give a concentration of 1.0 mol / L to obtain an electrolyte solution for a capacitor.

[0075] 《Example 2》

[0076] Triethylmethylammonium tetrafluoroborate was added to a solvent containing 90 parts by weight of propylene carbonate (manufactured by Tokyo Chemical Industry Co., Ltd.) and 10 parts by weight of Compound 2 at a concentration of 1.0 mol / L to obtain an electrolyte solution for a capacitor.

[0077] 《Example 3》

[0078] Triethylmethylammonium tetrafluoroborate was added to a solvent containing 90 parts by weight of propylene carbonate (manufactured by Tokyo Chemical Industry Co., Ltd.) and 10 parts by weight of Compound 3 so as to have a concentration of 1.0 mol / L to obtain an electrolyte solution for a capacitor.

[0079] <Production of laminated batteries>

[0080] A 30 mm wide and 20 μm thick aluminum sheet was prepared as a current collector, and activated carbon was coated on both sides with a thickness of 80 μm as an electrode. Next, the electrode was cut into 20×72 mm, and the electrode lead was welded to the aluminum surface of the current collector. A separator formed of cellulose with a thickness of 50 μm was clamped by a pair of electrodes and placed in a container made of aluminum laminate film, and an electrolyte was injected in a dry room to impregnate the electrode. Then, the container was sealed to make a laminated battery for a capacitor.

[0081] <Measurement of internal resistance>

[0082] A voltage of 3.0 V was applied to the fabricated capacitor, and its internal resistance was measured at -30°C.

[0083] Table 1 shows the relative values ​​of the internal resistance values ​​of each laminated battery at -30°C and the internal resistance value of Comparative Example 1.

[0084] [Table 1]

[0085] Relative value with Comparative Example 1 Comparative Example 1 1.0 Comparative Example 2 1.8 Comparative Example 3 1.5 Example 1 0.85 Example 2 0.93 Example 3 0.93

[0086] The results in Table 1 show that Examples 1 to 3 using compounds having 11 or less heavy atoms and one or more cyclopropane rings or aziridine rings have lower internal resistance values ​​than Comparative Example 1 using only propylene carbonate.

[0087] In addition, as in the case of Comparative Example 2, it is found that when a compound having 12 heavy atoms is used, the internal resistance value increases compared with Comparative Example 1. Furthermore, in Comparative Example 3, it is found that even if the compound having 11 heavy atoms or less has no cyclopropane ring or aziridine ring, the internal resistance value increases.

[0088] <Manufacturing of secondary batteries>

[0089] (negative electrode)

[0090] The negative electrode active material (graphite), sodium carboxymethylcellulose (CMC-Na) and styrene-butadiene rubber (SBR) were mixed at a mass ratio of 97.5:1:1.5, and after adding water, a mixer (manufactured by PRIMIX Corporation, TKHIBISCUSMIX) was used to stir the mixture to prepare a negative electrode mixture slurry. 2The negative electrode mixture slurry was applied so that the mass of the negative electrode mixture became 190 g, and after the coating was dried, it was rolled to form a copper foil with a density of 1.5 g / cm on both sides. 3 The negative electrode of the negative electrode mixture layer.

[0091] (positive electrode)

[0092] The lithium nickel composite oxide (LiNi 0.8 Co 0.18 Al 0.02 O2, acetylene black and polyvinylidene fluoride, after adding N-methyl-2-pyrrolidone (NMP), a mixer (made by PRIMIX Corporation, TKHIBISCUS MIX) was used to stir and prepare a slurry of the positive electrode mixture. Next, the slurry of the positive electrode mixture was applied to the surface of the aluminum foil, and after the coating was dried, it was rolled to form a 3.6 g / cm2 film on both sides of the aluminum foil. 3 The positive electrode of the positive electrode mixture layer.

[0093] 《Comparative Example 4》

[0094] A non-aqueous electrolyte was prepared by mixing ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) in a volume ratio of 20:70:10. LiPF6 was used as the lithium salt. The concentration of LiPF6 in the electrolyte was 1.2 mol / L.

[0095] 《Comparative Example 5》

[0096] A non-aqueous electrolyte was prepared by mixing ethylene carbonate (EC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and dibutyl carbonate (produced by Tokyo Chemical Industry Co., Ltd.) in a volume ratio of 18:63:9:10. LiPF6 was used as the lithium salt. The concentration of LiPF6 in the electrolyte was 1.2 mol / L.

[0097] 《Comparative Example 6》

[0098] A non-aqueous electrolyte was prepared by mixing ethylene carbonate (EC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and pimelic acid (produced by Tokyo Chemical Industry Co., Ltd.) in a volume ratio of 18:63:9:10. LiPF6 was used as the lithium salt. The concentration of LiPF6 in the electrolyte was 1.2 mol / L.

[0099] 《Example 4》

[0100] A non-aqueous electrolyte was prepared by mixing ethylene carbonate (EC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and compound 1 in a volume ratio of 18:63:9:10. LiPF6 was used as the lithium salt. The concentration of LiPF6 in the electrolyte was 1.2 mol / L.

[0101] 《Example 5》

[0102] A non-aqueous electrolyte was prepared by mixing ethylene carbonate (EC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and compound 2 in a volume ratio of 18:63:9:10. LiPF6 was used as the lithium salt. The concentration of LiPF6 in the electrolyte was 1.2 mol / L.

[0103] Example 6

[0104] A non-aqueous electrolyte was prepared by mixing ethylene carbonate (EC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and compound 3 in a volume ratio of 18:63:9:10. LiPF6 was used as the lithium salt. The concentration of LiPF6 in the electrolyte was 1.2 mol / L.

[0105] The tabs were mounted on each electrode, and the positive electrode and the negative electrode were wound into a spiral shape with the tabs located at the outermost periphery through the separator, thereby producing an electrode group. The electrode group was inserted into an outer shell made of an aluminum laminate film, vacuum dried at 105°C for 2 hours, and then injected with a non-aqueous electrolyte, and the opening of the outer shell was sealed to obtain a secondary battery.

[0106] <Measurement of discharge capacity (battery capacity)>

[0107] The secondary battery prepared as described above was charged at a constant current of 0.3 It (800 mA) at -5°C until the voltage reached 4.2 V, and then charged at a constant voltage of 4.2 V until the current reached 0.015 It (40 mA). Then, the battery was discharged at a constant current of 0.3 It (800 mA) until the voltage reached 2.75 V. The discharge capacity at this time was determined as the battery capacity.

[0108] Table 2 shows the relative values ​​of the battery capacity of each secondary battery at -5°C measured in this way and the battery capacity of Comparative Example 4.

[0109] [Table 2]

[0110] Relative value with Comparative Example 1 Comparative Example 4 1.0 Comparative Example 5 0.6 Comparative Example 6 0.8 Example 4 1.2 Example 5 1.1 Example 6 1.1

[0111] From the results in Table 2, it can be seen that in Examples 4 to 6 using compounds having 11 or less heavy atoms and having one or more cyclopropane rings or aziridine rings, the battery capacity is increased compared to Comparative Example 4 using an electrolyte solution not containing such a compound. In addition, as in the case of Comparative Example 5, it can be seen that when a compound having 12 heavy atoms is used, the battery capacity is reduced compared to Comparative Example 4. Furthermore, in Comparative Example 6, it can be seen that even if the compound has 11 or less heavy atoms, the battery capacity is reduced if it does not have a cyclopropane ring or an aziridine ring.

[0112] It is found that the internal resistance of the element can be reduced and the operating characteristics at low temperatures can be improved by using the electrolyte material disclosed in the present invention.

[0113] "appendix"

[0114] According to the description of the above embodiments, the following technology is disclosed.

[0115] (Technology 1)

[0116] An electrolyte solution comprising a non-aqueous solvent and an electrolyte dissolved in the non-aqueous solvent,

[0117] The nonaqueous solvent contains a first compound having 11 or less heavy atoms and one or more cyclopropane rings or aziridine rings.

[0118] (Technique 2)

[0119] The electrolyte solution according to technology 1, wherein the first compound is any one of the following compounds 1 to 3,

[0120]

[0121] (Technique 3)

[0122] The electrolyte solution according to the technique 1 or 2, wherein the content of the first compound is 5 mass % or more and 80 mass % or less.

[0123] (Technique 4)

[0124] The electrolyte solution according to any one of techniques 1 to 3, wherein the nonaqueous solvent further contains a second compound selected from the group consisting of γ-butyrolactone, vinylene carbonate, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate and 3-methylsulfolane.

[0125] (Technique 5)

[0126] The electrolytic solution according to any one of techniques 1 to 4, wherein the electrolyte contains a quaternary ammonium salt or a lithium salt.

[0127] (Technique 6)

[0128] The electrolyte according to technology 5, wherein the quaternary ammonium salt includes a salt formed of a tetraalkylammonium ion and an anion.

[0129] (Technique 7)

[0130] The electrolyte according to technology 6, wherein the tetraalkylammonium ion contains at least one selected from the group consisting of tetramethylammonium ion, trimethylethylammonium ion, triethylmethylammonium ion, tetraethylammonium ion, tetrabutylammonium ion, and diethyldimethylammonium ion.

[0131] (Technology 8)

[0132] The electrolyte according to technology 6 or 7, wherein the anion contains a selected from Cl - 、BF4 - PF6 - 、ClCO4 - CF3SO3 - 、N(FSO2)2 - 、N(CF3SO2)2 - 、N(C2F5SO2)2 - , and C(CF3SO2)3 - The anions in the group.

[0133] (Technique 9)

[0134] According to the electrolyte described in Technology 5, the quaternary ammonium salt is triethylmethylammonium tetrafluoroborate, and the lithium salt is LiPF6.

[0135] (Technology 10)

[0136] The electrolyte according to technology 5, wherein the content of the quaternary ammonium salt or the lithium salt in the electrolyte is 0.1 mol / L or more and 3.0 mol / L or less.

[0137] (Technology 11)

[0138] The electrolyte according to technology 5, wherein the content of the quaternary ammonium salt or the lithium salt in the electrolyte is 0.5 mol / L or more and 2.0 mol / L or less.

[0139] (Technology 12)

[0140] A power storage element comprising the electrolytic solution according to any one of techniques 1 to 11.

[0141] (Technology 13)

[0142] A compound having the structure of any of the following compounds 1 to 3,

[0143]

[0144] (Technology 14)

[0145] An electrolyte additive having the structure of any of the following compounds 1 to 3,

[0146]

[0147] The present invention has been described with respect to presently preferred embodiments, but such disclosure is not to be construed as limiting. Various modifications and changes should be apparent to those skilled in the art in the art to which the present invention belongs upon reading the above disclosure. Therefore, the appended claims should be construed as including all modifications and changes without departing from the spirit and scope of the present invention.

[0148] Industrial Applicability

[0149] The electrolyte solution disclosed herein is used in a storage element such as a non-aqueous electrolyte capacitor and a non-aqueous electrolyte secondary battery. The storage element disclosed herein is useful as a main power source for mobile communication devices, portable electronic devices, and the like.

[0150] Description of Reference Numerals

[0151] 1 Electrode set

[0152] 2 Positive lead

[0153] 3 Negative lead

[0154] 4 Battery housing

[0155] 5 Sealing plate

[0156] 6 Negative terminal

[0157] 7 Gasket

Claims

1. An electrolyte solution comprising: a non-aqueous solvent and an electrolyte dissolved in the non-aqueous solvent, The nonaqueous solvent contains a first compound having 11 or less heavy atoms and one or more cyclopropane rings or aziridine rings.

2. The electrolyte according to claim 1, wherein The first compound is any one of the following compounds 1 to 3, 3. The electrolyte according to claim 1, wherein The content of the first compound is 5 mass % or more and 80 mass % or less.

4. The electrolyte according to claim 1, wherein The nonaqueous solvent further contains a second compound selected from the group consisting of γ-butyrolactone, vinylene carbonate, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and 3-methylsulfolane.

5. The electrolyte according to claim 1, wherein The electrolyte includes a quaternary ammonium salt or a lithium salt.

6. The electrolyte according to claim 5, wherein The quaternary ammonium salt includes a salt formed from a tetraalkylammonium ion and an anion.

7. The electrolyte according to claim 6, wherein The tetraalkylammonium ion includes at least one selected from the group consisting of a tetramethylammonium ion, a trimethylethylammonium ion, a triethylmethylammonium ion, a tetraethylammonium ion, a tetrabutylammonium ion, and a diethyldimethylammonium ion.

8. The electrolyte according to claim 6, wherein The anion contains a member selected from the group consisting of Cl - 、BF4 - PF6 - 、ClCO4 - CF3SO3 - 、N(FSO2)2 - 、N(CF3SO2)2 - 、N(C2F5SO2)2 - and C(CF3SO2)3 - The anions in the group.

9. The electrolyte according to claim 5, wherein The quaternary ammonium salt is triethylmethylammonium tetrafluoroborate, and the lithium salt is LiPF6.

10. The electrolyte according to claim 5, wherein In the electrolyte solution, a content rate of the quaternary ammonium salt or the lithium salt is 0.1 mol / L or more and 3.0 mol / L or less.

11. The electrolyte according to claim 5, wherein In the electrolyte solution, a content rate of the quaternary ammonium salt or the lithium salt is 0.5 mol / L or more and 2.0 mol / L or less. 12 . An electric storage element comprising the electrolytic solution according to claim 1 .

13. A compound having the structure of any of the following compounds 1 to 3,

Citation Information

Patent Citations

  • Electric double layer capacitor

    JP2000114105A

  • Electrolyte solution for capacitors, electric double layer capacitor, and lithium ion capacitor

    WO2013146136A1